PELATIHAN PERAWATAN KENDARAAN RODA DUA BAGI MASYARAKAT DI DUSUN CITEUREUP 1 - Ibnu Mutaqien; Anisa Putri; Diana Fajarwati (Universitas Islam 45 Bekasi, 2022)
Motorcycles are a means of transportation that are often used in daily activities, increasingly sophisticated technological developments have begun to be combined with the help of electronic control circuits such as an injection system to control combustion in the motorcycle combustion chamber or indicators to show a hot engine temperature that makes it easier for motorcycle owners to maintain the vehicle. Therefore, because of the lack of workshops or vehicle service services here the author will share information about motorcycle maintenance that can be done alone to save costs and can be developed as a form of business, such as a workshop. With the lack of information, most people only use motorbikes for their daily needs and ignore motorbike maintenance. Here the author will educate the community on how to take care of their two-wheeled vehicles in the citeureup 1 hamlet with methods of socializing the importance of caring for two-wheeled vehicles, training on caring for two-wheeled vehicles, and evaluating to ensure that people can take care of their own motorbikes. This program also has the aim that the people of Citeureup 1 Hamlet, Kutamukti Village, Kutawaluya District, Karawang Regency are able to maintain their own motorcycles and can be developed as a form of business, namely workshops.